Public policy in the face of post-truth politics and the role of deliberation - Piyapong Boossabong (2020)
© 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group. By learning from haze pollution policy in Chiang Mai, Thailand, the policy intervention discussed here is based on blaming rural farmers as a cause of the problem. The main policy instrument, thus, is to prohibit farmers from burning. Scientists point out that this complex problem is related to climate change, however, there is little focus on individual contributions to the problem. People find it more convenient to watch governmental agencies victimize farmers, since such a manipulation of the truth is politically and socially constructed. This challenge derives from the fact that some facts are perceived when making a policy, while some are ignored. Also, some facts are selected when evaluating a policy, while others are not. This article claims that joint-fact checking can help us to cope with the challenge when it operates through a deliberative process in which both empirical and normative assumptions are included.